Different Approaches for Multiband Transport in Semiconductors - Borgioli, G.; Frosali, G.; Modugno, M.; Morandi, O. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We compare the well-known Kane model with a new multiband envelope function model, which presents many advantages with respect to the first one.